IMPLEMENTASI PENDIDIKAN KARAKTER DENGAN POLA INTEGRALISTIK DALAM MEMBENTUK KEPRIBADIAN SISWA DI SDIT BUNAYYA PADANGSIDIMPUAN - Zulhimma, Zulhimma (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2014)
AbstractCharacter education is a cultivation system of values of the character of the child, which includes knowledge, consciousness or volition, and actions to implement these values, both to God, ourselves, others, the environment, or nationality to become a good person. Character education should be imparted to the students with integrative pattern to shape the personality of the students. In character education in schools, all components must be involved, including components - components of education itself, ie the content of the curriculum, learning and assessment, quality of relationships, handling or management of subjects, school management, the implementation of the activities or curricular activities, empowering infrastructure , financing, and work ethos throughout the school community and the environment. All the above elements should be integrated education as a whole in establishing the character of students.Kata Kunci: Pendidikan, Karakter, integralistik, kepribadian